Unlocking Public Value - Martin Cole , Greg Parston (John Wiley & Sons, Inc., Hoboken, 2006)
Among the many admirable aims of the environmental movement, the one that strikes me as most useful to those in public services is captured by the motto, â€œThink globally, act locally.â€ In a public services career spanning more than 35 years, I have had a chance to look at public service systems in the Americas, Europe and Africa. I have been forcibly struck by the need to give substantial weight to the local political and cultural context of a particular system. You ignore a genuine understanding of these features at your peril: You, the public services administrator or elected official, must be seen to listen and pay attention to local priorities. In other words, act locally. At the same time, my experience in South Africa and Canada (which in key ways face vastly different challenges) and elsewhere is that there are some major global economic, human and social drivers that all politicians and public service administrators need to take account of in their engagement with their citizens. Think globally. In Unlocking Public Value, Marty Cole and Greg Parston offer public services practitioners a unique tool to help them capture the mix of goals or outcomes, some reflecting local, some global, concerns, and measure performance in attaining these outcomes. Providing a framework and step-by-step process for defining these outcomes is one of the key achievements of the book. Since nearly all meaningful outcomes come at a cost to taxpayers, the measuring of outcomes occurs in the context of tracking not just costs, but cost-effectiveness as well.